Enterobacter aerogenes and Enterobacter cloacae; versatile bacterial pathogens confronting antibiotic treatment - Davin-Regli, Anne; Pagès, Jean-Marie (Frontiers in Microbiology, 2015)
Enterobacter aerogenes and E. cloacae have been reported as important opportunistic and multiresistant bacterial pathogens for humans during the last three decades in hospital wards. These Gram-negative bacteria have been largely described during several outbreaks of hospital-acquired infections in Europe and particularly in France. The dissemination of Enterobacter spp is associated with the presence of redundant regulatory cascades that efficiently control the membrane permeability ensuring the bacterial protection and the expression of detoxifying enzymes involved in antibiotic degradation/inactivation. In addition, these bacterial species are able to acquire numerous genetic mobile elements that strongly contribute to antibiotic resistance. Moreover, this particular fitness help them to colonize several environments and hosts and rapidly and efficiently adapt their metabolism and physiology to external conditions and environmental stresses. Enterobacter is a versatile bacterium able to promptly respond to the antibiotic treatment in the colonized patient. The balance of the prevalence, E. aerogenes versus E. cloacae, in the reported hospital infections during the last period, questions about the horizontal transmission of mobile elements containing antibiotic resistance genes e.g. the efficacy of the exchange of resistance genes Klebsiella pneumoniae to Enterobacter spp. It is also important to mention the possible role of antibiotic use in the treatment of bacterial infectious diseases in this E. aerogenes / E. cloacae evolution.